2019
DOI: 10.3390/e21030309
|View full text |Cite
|
Sign up to set email alerts
|

A Fractional-Order Partially Non-Linear Model of a Laboratory Prototype of Hydraulic Canal System

Abstract: This article addresses the identification of the nonlinear dynamics of the main pool of a laboratory hydraulic canal installed in the University of Castilla La Mancha. A new dynamic model has been developed by taking into account the measurement errors caused by the different parts of our experimental setup: (a) the nonlinearity associated to the input signal, which is caused by the movements of the upstream gate, is avoided by using a nonlinear equivalent upstream gate model, (b) the nonlinearity associated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Theoretical and practical studies have demonstrated the advantages of using fractional calculus in the modelling and control of dynamic systems, mainly from an industrial process control point of view [1,2]. For instance, in process modelling, several works (see, for example [3][4][5][6][7][8][9][10][11]) have shown that fractional order models with one or two fractional parameters can represent the process dynamics better than integer transfer functions of low order, such as the well-known first order plus dead time (FOPDT) and second order plus dead time (SOPDT) models. Therefore, a wider range of real-world processes can be modeled and an improved control system design can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and practical studies have demonstrated the advantages of using fractional calculus in the modelling and control of dynamic systems, mainly from an industrial process control point of view [1,2]. For instance, in process modelling, several works (see, for example [3][4][5][6][7][8][9][10][11]) have shown that fractional order models with one or two fractional parameters can represent the process dynamics better than integer transfer functions of low order, such as the well-known first order plus dead time (FOPDT) and second order plus dead time (SOPDT) models. Therefore, a wider range of real-world processes can be modeled and an improved control system design can be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Water scarcity has become a progressively growing problem worldwide due to the accelerated increase in water demand, which is expanding nowadays at a rate never seen before in any previous time [1][2][3][4][5]. Therefore, the effective management of water resources is a challenge to face the complexity of the real problem [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A new dynamic model is developed by taking into account the measurement errors caused by the different parts of the experimental setup. Fractional and integer order plus time delay models are used to approximate the responses of the main pool of the canal in its different flow regimes [ 1 ].…”
mentioning
confidence: 99%